EVALUASI TINGKAT KEPUASAN PENGGUNA LULUSAN TERHADAP ALUMNI IAIN LHOKSEUMAWE - Muhammad Ilham; Dwhy Dinda Sari; Muhammad Anggung Manumanoso Prasteyo (PENCERAHAN, 2022)
This study seeks to assess the outcomes of graduate user satisfaction from numerous aspects that are measured to determine the trend, using a quantitative approach and a survey form as a tool to achieve the results of this study. Soft skills and talent were examined in addition to ethical, communication, and self-development, which are classified as social indicators. With 421 respondents, the appraised indication was hard skill as fundamental abilities of graduate in understanding foreign language and computer technology. The descriptive analytic technique was used to get the outcome, and the graduate's user was pleased with the soft and hard abilities of the IAIN Lhokseumawe graduates. This is supported by the pattern of graduating user evaluations highlighting the good benchmarks. The highest levels of user happiness may be observed ethically. In other words, 91 percent of graduate users were satisfied.